Analysis of Factors that Influence the Effectiveness of Academic Mentoring Programs on Student Academic Success Mediated by Academic Culture Variables (Study at the Faculty of Economics, Mayjen Sungkono University, Mojokerto) - Lukito, Harjo; Agustina, Ratna; Ariwidodo, Dadang Purwo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is a quantitative study with a non-experimental correlational survey approach, aimed at developing and testing a theory about the influence of various factors on student academic success with academic culture as a mediator. The research population was class 8 C (PMSR) at the Faculty of Economics, Mayjen Sungkono University, Mojokerto, totaling 41 people. Data was collected through a questionnaire that measured the quality of mentoring, materials, methods, student participation, institutional support, evaluation and feedback, learning environment, academic culture, and academic success using a Likert scale. Data analysis used SmartPLS version 4.1.0.2 via Partial Least Square (PLS) analysis. The results show that the quality of mentoring, mentoring methods, and institutional support significantly improve students' academic achievement with academic culture as an important mediator.